Agent-based Modeling and Simulation as an Alternative for the Study of Business Organizations (2017)
Introduction: The article arises from the research Agent-based modeling and simulation as an alternative for the study of business organizations, conducted during 2016 at the Universidad Distrital Francisco José de Caldas, Bogotá. The authors summarize the most outstanding literature published on the modeling and simulation of complex systems throughout history, particularly agent-based models, in order to form an opinion on their possible contributions to management research. Method: We analyzed the information collected from scientific articles in ProQuest and Scopus databases from 1990 to date, including key concepts of modeling and simulation, based on agents described in some books. Results: Traditional approaches, characterized by the use of statistics and classical mathematics, are not relevant to model organizations because of their deterministic and reductionist view. Therefore, an alternative approach is presented for the study of organizations that are found in the modeling and simulation techniques of the sciences of complexity, whose purpose is to study systems characterized by emerging behaviors. Conclusions: Despite its low popularity, the implementation of these alternatives cannot only benefit organizations, but can also contribute to the creation of guidelines for greater appropriation of simulation models for organizations.